Effect of Waste Glass on Properties of Treated Problematic Soils: A Comprehensive Review - Sherwany, Jaylan H.; Kakrasul, Jamal I.; Han, Jie (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Soils are the most commonly used construction material in engineering projects. Fine-grained soils especially clayey soil may expand and lose strength when wet and shrink when dry, resulting in a significant volume change. Construction on weak soils has created challenges for various civil engineering projects worldwide, including roadways, embankments, and foundations. As a result, improving weak soil is vital, particularly for highway construction. The properties of this type of soil can be improved by waste-recycled materials such as waste glass (WG). The WG must be crushed and ground to a fine powder first and then can be mixed in various proportions with the soil. The primary objective of this study is to review the effect of WG on geotechnical properties of fine-grained soils treated by WG. To demonstrate the effects, the treated fine-grained soils at varying percentages of WG are compared with untreated soils. Physical properties (e.g., Atterberg limits, swelling, and maximum dry density), mechanical properties (e.g., California bearing ratio, and unconfined compressive strength) are evaluated. The test results from the literature show that adding a certain percentage of WG leads to a substantial effect on the properties of fine-grained soils; hence, using WG could reduce the required thickness of subbases in the construction of driveways and roads.